UMP-MOHE JAKM Outreach Programme focuses on Social Innovation and STEM - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 28 October 2022 - The UMP-MOHE Outreach Programme through Jelajah Aspirasi Keluarga Malaysia (JAKM) Pahang 2022 recently welcomed students of Sekolah Menengah Kebangsaan Indera Shahbandar (SMKIS) when 50 students had the opportunity to learn the basics of electricity and electronics by using interactive electronic blocks and building simple circuits of various applications.